Metode Pembelajaran PAI untuk Siswa Tunadaksa - Kristiyanto, Risky; Muhaimin, Agung Nuryahya; Aryanto, Avif; Salsabila, Fadilah; Husna, Difa’ul (Lembaga Yasin AlSys, 2023)
This study aims to characterize and develop Islamic education services for disabled children. The type of research used in this research is library research, to discuss how Islamic Religious Education learning methods and services are for students with special needs with disabilities. Data collection techniques use documentation techniques by collecting data through data source documents such as books, journals and scientific articles. The results of the study show that there are several characteristics of children with physical impairment, including: physical characteristics, academic characteristics, and social or emotional characteristics. Children with special needs who experience damage or loss of physical members, the process of developing Islamic religious education materials in providing material or teaching methods is almost the same as children with visual impairments and hearing impairments. Meanwhile, the development model for disabled children is through the school environment, family environment, and community environment.